RASSF1A suppresses estrogen-dependent breast cancer cell growth through inhibition of the yes-associated protein 1 (YAP1), inhibition of the Forkhead Box Protein M1 (FOXM1), and activation of Forkhead Box Transcription Factor 3A (FOXO3A) - Roßwag, Sven; Thiede, Gitta; Sleeman, Jonathan P.; Thaler, Sonja (Cancers, 2020)
The estrogen receptor alpha (ERα) is expressed by the majority of breast cancers and plays an important role in breast cancer development and tumor outgrowth. Although ERα is well known to be a specific and efficient therapeutic target, the molecular mechanisms that are responsible for the control of ERα expression and function in the context of breast cancer initiation and progression are complex and not completely elucidated. In previous work, we have demonstrated that the tumor suppressor RASSF1A inhibits ERα expression and function in ERα-positive breast cancer cells through an AKT-dependent mechanism. Transcriptional activators such as forkhead box protein M1 (FOXM1) and forkhead transcription factor 3A (FOXO3A) and signaling pathways such as the Hippo pathway are also known to modulate ERα expression and activity. Here we report that RASSF1A acts as an inhibitor of ERα-driven breast cancer cell growth through a complex, hierarchically organized network that initially involves suppression of the Hippo effector Yes-associated protein 1 (YAP1), which is followed by inhibition of AKT1 activity, increased FOXO3A activity as well as a blockade of FOXM1 and ERα expression. Together our findings provide important new mechanistic insights into how the loss of RASSF1A contributes to ERα+ breast cancer initiation and progression.